2018
DOI: 10.1177/0963689718771885
|View full text |Cite
|
Sign up to set email alerts
|

Single-Factor SOX2 Mediates Direct Neural Reprogramming of Human Mesenchymal Stem Cells via Transfection of In Vitro Transcribed mRNA

Abstract: Neural stem cells (NSCs) are a prominent cell source for understanding neural pathogenesis and for developing therapeutic applications to treat neurodegenerative disease because of their regenerative capacity and multipotency. Recently, a variety of cellular reprogramming technologies have been developed to facilitate in vitro generation of NSCs, called induced NSCs (iNSCs). However, the genetic safety aspects of established virus-based reprogramming methods have been considered, and non-integrating reprogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
(75 reference statements)
0
30
0
Order By: Relevance
“…Two studies reported that lentivirus-mediated expression of OCT4 is sufficient to obtain iNSCs from adult human fibroblasts, neonatal cord, and peripheral blood cells [29,30]. Besides Oct4, also Sox2 has been reported to be sufficient for direct conversion of somatic cells into iNSCs [32][33][34]. Dual SMAD inhibition is known to efficiently and rapidly convert pluripotent cells into neural cells [31], potentially indicating that reprogrammed cells might have passed a transient pluripotent stage.…”
Section: Transcription Factors Employed In Insc Generationmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies reported that lentivirus-mediated expression of OCT4 is sufficient to obtain iNSCs from adult human fibroblasts, neonatal cord, and peripheral blood cells [29,30]. Besides Oct4, also Sox2 has been reported to be sufficient for direct conversion of somatic cells into iNSCs [32][33][34]. Dual SMAD inhibition is known to efficiently and rapidly convert pluripotent cells into neural cells [31], potentially indicating that reprogrammed cells might have passed a transient pluripotent stage.…”
Section: Transcription Factors Employed In Insc Generationmentioning
confidence: 99%
“…A key question to assess the outcome of direct conversion strategies is to which extent directly converted iNSCs recapitulate these characteristics [11,71]. In order to demonstrate selfrenewal potential and clonal growth ability, iNSCs were either cultivated as primary and secondary neurospheres [33,34], analyzed in colony formation assays [28,33,36,39,42,48,72], and/or passaged several times [11,13,14,26,30,32,33,38,57,59,60,73]. On the other hand, all iNSC populations have been reported to express pan-neural markers, to be at least bipotential, and to show self-renewal and clonal growth ( Table 2).…”
Section: Molecular and Cellular Characterization Of Inscsmentioning
confidence: 99%
See 3 more Smart Citations